2016
DOI: 10.3389/fnhum.2016.00312
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying Sad Music: Paradox or Parallel Processes?

Abstract: Enjoyment of negative emotions in music is seen by many as a paradox. This article argues that the paradox exists because it is difficult to view the process that generates enjoyment as being part of the same system that also generates the subjective negative feeling. Compensation theories explain the paradox as the compensation of a negative emotion by the concomitant presence of one or more positive emotions. But compensation brings us no closer to explaining the paradox because it does not explain how exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
3
35
0
3
Order By: Relevance
“…First, we examined whether negative emotion evoked by music could be enjoyed, and under what circumstances. In line with a growing body of evidence for the ‘paradoxical’ effect of enjoyment of negative emotions in music [20], a subset of our sample reported high enjoyment of self-selected music that was strongly evocative of negative emotions. Crucially, we found that this subgroup of individuals tended to be those with a (trait) propensity to be highly absorbed.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…First, we examined whether negative emotion evoked by music could be enjoyed, and under what circumstances. In line with a growing body of evidence for the ‘paradoxical’ effect of enjoyment of negative emotions in music [20], a subset of our sample reported high enjoyment of self-selected music that was strongly evocative of negative emotions. Crucially, we found that this subgroup of individuals tended to be those with a (trait) propensity to be highly absorbed.…”
Section: Discussionsupporting
confidence: 71%
“…This scepticism stems from the idea that negative emotions, such as sadness and grief, are associated with withdrawal and aversion under normal circumstances. Thus, there must be some extenuating circumstance to explain the concomitant pleasure response, and as such, ‘real’ negative emotion is not experienced [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Listening to music affects people's emotional states, but can be considered ambiguous in terms of its emotional content and not communicate discrete emotions . For example, “sad” music can be experienced as sad as well as pleasurable . When music is contextualized (e.g., with lyrics, mental imagery), the emotional ambiguity is reduced, and it becomes one of the most powerful and widely used techniques for mood induction .…”
Section: Introductionmentioning
confidence: 99%
“…But some philosophers and psychologists are also interested in explaining what the various components might be, and how they fit together. In the psychological literature Scherer's (1984) component processes model of emotion has motivation-change as one of its components, which aligns with the concept of affect-valence (Schubert, 2016). Schubert (2013b) applied these ideas to explain how it was that people could enjoy music that evoked negative emotion.…”
Section: Affect-valence and Emotion-valencementioning
confidence: 99%
“…But some philosophers and psychologists are also interested in explaining what the various components might be, and how they fit together. In the psychological literature Scherer's (1984) component processes model of emotion has motivation-change as one of its components, which aligns with the concept of affect-valence (Schubert, 2016).Schubert (2013b) applied these ideas to explain how it was that people could enjoy music that evoked negative emotion. In that study he argued that to better understand emotional and preference relationships with music, one must not only vary the kind of emotions evoked (as was typical in music psychology research on emotion), but also vary the preference level.…”
mentioning
confidence: 99%